2021
DOI: 10.1002/ange.202011722
|View full text |Cite
|
Sign up to set email alerts
|

Stable Dioxin‐Linked Metallophthalocyanine Covalent Organic Frameworks (COFs) as Photo‐Coupled Electrocatalysts for CO2Reduction

Abstract: In this work, we rationally designed a series of crystalline and stable dioxin‐linked metallophthalocyanine covalent organic frameworks (COFs; MPc‐TFPN COF, M=Ni, Co, Zn) under the guidance of reticular chemistry. As a novel single‐site catalysts (SSCs), NiPc/CoPc‐TFPN COF exhibited outstanding activity and selectivity for electrocatalytic CO2 reduction (ECR; Faradaic efficiency of CO (FECO)=99.8(±1.24) %/ 96.1(±1.25) % for NiPc/CoPc‐TFPN COF). More importantly, when coupled with light, the FECO and current de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…Covalent organic frameworks (COFs) are unique porous two- or three-dimensional materials with highly ordered crystalline structures. Their diverse functional encodes are able to be programmed by smart reaction of versatile molecular building blocks under the guidance of the topological design diagram. Since 2005, COFs have been rapidly developing, further enforcing the advancement of functional organic materials toward gas storage, separation, ,, catalysis, ion conduction, and energy storage. , COFs allow for atomically precise integration of functional modules into periodic arrangement around highly ordered open porosities, usually generating the unilateral materials with reinforced properties. Although the strategic implant of two kinds of useful organic units has been conceived to provide interesting tailored COFs, ,,, few examples with multiple and synergistic functions have been reported due possibly to the limitation of modules possessing suitable reactivity, matched electronic levels, compatible topology, and excellent crystallinity.…”
Section: Introductionmentioning
confidence: 99%
“…Covalent organic frameworks (COFs) are unique porous two- or three-dimensional materials with highly ordered crystalline structures. Their diverse functional encodes are able to be programmed by smart reaction of versatile molecular building blocks under the guidance of the topological design diagram. Since 2005, COFs have been rapidly developing, further enforcing the advancement of functional organic materials toward gas storage, separation, ,, catalysis, ion conduction, and energy storage. , COFs allow for atomically precise integration of functional modules into periodic arrangement around highly ordered open porosities, usually generating the unilateral materials with reinforced properties. Although the strategic implant of two kinds of useful organic units has been conceived to provide interesting tailored COFs, ,,, few examples with multiple and synergistic functions have been reported due possibly to the limitation of modules possessing suitable reactivity, matched electronic levels, compatible topology, and excellent crystallinity.…”
Section: Introductionmentioning
confidence: 99%
“…For the first time, Lan's group published dioxin-linked metallophthalocyanine covalent organic frameworks as photo-coupled CO 2 reduction electrocatalysts in 2020. 126 In this study, they designed a series of crystalline and stable dioxin-linked metallophthalocyanine covalent organic frameworks (MPc-TFPN COF, M = Ni, Co, Zn), among which NiPc/CoPc-TFPN COF showed excellent activity for CO 2 reduction when coupled with light compared to a dark environment. The reaction mechanism was also studied by DFT, which revealed that an external light field can improve the electron transfer to the adsorbed CO 2 in phthalocyanine COFs leading to the favorable CO 2 .…”
Section: Applicationmentioning
confidence: 99%
“…Up to now, a variety of nanomaterials with good controlled-release properties have been reported, including poly­(vinyl alcohol) microspheres in a silk sericin-based hydrogel, composite films with an adjustable number of layers using sodium alginate (SA), chitosan (CS), and activated charcoal (AC), microcrystals, polyvinyl alcohol/chitosan microspheres, and a selenium-rich tea set. , Chitosan (CS) has antibacterial properties due to the interaction between its positively charged amino group and the negatively charged cell membrane of bacteria. , The nanocapsules made from CS exhibit typical pH response characteristics due to the large number of amino groups contained in the side chain. , In addition, the intelligent delivery of fungicides can be realized by the modification of chitosan. , Our research group has developed a capsaicin@chitosan (CAP@CS) microcapsule with pH response performance, which can realize the intelligent controlled release of the natural bactericide CAP, which plays an effective sterilization and antifouling role. , However, its dispersion is limited. In order to improve the dispersion on the basis of pH response sterilization, we hope to introduce other materials to further improve the performance of intelligent response controlled release sterilization. , Two-dimensional materials (graphene, covalent organic frameworks) have great potential for marine protective materials, such as corrosion protection and fouling protection, due to their excellent adsorption characteristics, mechanical strength, thermal stability, and other characteristics. , In recent years, 2D covalent organic frameworks (COFs), which are typical representatives of 2D nanomaterials, have the characteristics of diverse synthesis methods, large specific surface area, stable physical and chemical properties, and broad application prospects in different fields. , COF-MOF hybrid materials have ingenious and obvious structural characteristics and excellent performance . A novel ionic covalent organic framework (iCOF) containing guanidine can be used as a potential candidate for extracting uranium from seawater .…”
Section: Introductionmentioning
confidence: 99%
“…45,46 In recent years, 2D covalent organic frameworks (COFs), which are typical representatives of 2D nanomaterials, have the characteristics of diverse synthesis methods, large specific surface area, stable physical and chemical properties, and broad application prospects in different fields. 47,48 COF-MOF hybrid materials have ingenious and obvious structural characteristics and excellent performance. 49 A novel ionic covalent organic framework (iCOF) containing guanidine can be used as a potential candidate for extracting uranium from seawater.…”
Section: Introductionmentioning
confidence: 99%